Implementasi Pendidikan Kewarganegaraan dalam Membentuk Karakter Jujur dan Tanggung Jawab - Uswatun Hasanah; Ribut Prastiwi (ASANKA: Journal of Social Science And Education, 2021)
One of the impacts of globalization is the lack of optimal moral value not only among the people but also in the world of politics and education. This study aims to determine the implementation of civic education in shaping the honest character and responsibility of students. This research is a qualitative descriptive research. The subjects studied were school principals, civic teachers and students. This study uses data collection techniques in the form of observation, interviews and documentation. The results of the study indicate that the implementation of civic education in shaping the honest character and responsibilities of students included three aspects, namely planning, implementation and evaluation.